2004
DOI: 10.1088/0957-4484/15/4/028
|View full text |Cite
|
Sign up to set email alerts
|

Field effect transistors based on poly(3-hexylthiophene) at different length scales

Abstract: In this paper we report on thin film transistors based on drop casting solutions of regioregular poly(3-hexylthiophene) (P3HT) over prefabricated gold electrodes. This polymer is known to self-organize into a lamellar structure in chloroform resulting in high field-effect mobilities. We studied the dependency of the charge carrier mobility of devices prepared from solution in chloroform with electrode spacings ranging from 5 µm to 20 nm. It was found that the overall trend was that the mobility decreased as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 20 publications
(24 reference statements)
1
72
0
Order By: Relevance
“…2͒, the absence of well-defined potential barriers associated with grain boundaries in scanning kelvin probe potential imaging 60 and with previous measurements on individual P3HT nanofibers, which showed no evidence of an enhanced field-effect mobility in spite of grain boundary effects being eliminated in such experiments. 24,35 Further breakthroughs to achieve even higher mobilities in crystalline polymers such as P3HT require unique processes to better control the various factors that determine the crystal growth and the chain conformation, and to improve the crystalline quality and eliminate structural and chemical defects in high MW P3HT nanoribbon crystals. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2͒, the absence of well-defined potential barriers associated with grain boundaries in scanning kelvin probe potential imaging 60 and with previous measurements on individual P3HT nanofibers, which showed no evidence of an enhanced field-effect mobility in spite of grain boundary effects being eliminated in such experiments. 24,35 Further breakthroughs to achieve even higher mobilities in crystalline polymers such as P3HT require unique processes to better control the various factors that determine the crystal growth and the chain conformation, and to improve the crystalline quality and eliminate structural and chemical defects in high MW P3HT nanoribbon crystals. …”
Section: Discussionmentioning
confidence: 99%
“…We observe that the saturation mobility of different MW generally increases as channel length decreases, which is opposite to the reduction of mobility caused by severe contact limited short-channel transistors with Cr-Au or Ti-Au electrodes. 23,24 The mobility is found to be more strongly channel-length dependent in low-mobility transistors, but little dependence is seen in highly crystalline, high-MW transistors. Figure 3 shows the output characteristics of 2 m-and 20 m-channel TCB spin-cast transistors plotted on a current scale normalized by the channel length L. The 20 m-channel transistors for both low ͑a͒ and high MW ͑b͒ polymers exhibit nearly ideal scaling characteristics.…”
Section: Transistor Characterizationmentioning
confidence: 99%
“…[140,141] The applied field induces a dipole in conducting elements, and pulls them towards the region where the field gradient is the highest. [142] Recently, it was demonstrated that P3HT fibers can also be aligned based on this method. Films of aligned fibers showed mobilities of 0.04 cm 2 V À1 s À1 .…”
mentioning
confidence: 99%
“…On the other hand, the 'face-on' arrangement, with DLC columnar directors perpendicular to the substrate, is generally best for photovoltaic devices and light emitting diodes. [10] Recently, various alignment techniques utilizing temperature gradient, [11] concentration gradient, [12] pre-aligned layer, [13] electric field [14] and magnetic field [15] have been reported. However, more facile approaches to achieve uniaxially oriented long-range ordering of DLC columnar superstructures with clear identification of the ordered structures are still being actively explored.…”
mentioning
confidence: 99%